Inequality in emissions: Evidence from Indonesian households - Mohammad Iqbal Irfany (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
Although the literature on emission inequality is abundant, this study will differentiate itself by focusing on emission inequalities at the household level due to the disparity in household expenditure profiles. We further separate measures on emission inequality based on household characteristics as well as decompose it into sources of emission. Employing a common application for analyzing inequalities, results show that as per capita expenditure increases, within quintiles emission inequality tends to decline until the middle quintiles but then further increases in expenditure level and worsens emission inequality until the richest household. The decomposition of inequality based on emission sources suggests that energy-transportation dominantly contributes of the overall emission inequality.
Keywords: O12; O13; D12; D63; 330; carbon footprint; household; inequality